The study of activated carbon derived from rubberwood sawdust (heavea brasiliensis): textural and chemical characterization / Collin G. Joseph, Faujan B.H. Ahmad and Lawrence Teo Kah Hoong - Joseph, Collin G; Ahmad, Faujan B.H.; Lawrence, Teo Kah Hoong (2006)
This present work comprehensively addresses the effects of using dehydrating agents such as potassium hydroxide on activated carbons prepared from rubber wood sawdust (RW). A two-stage activation process method was used; with semi-carbonization stage at 200°C for 15 minutes as the first stage followed by an activation stage at 500°C for 45 minutes as the second stage, The precursor material with the impregnation agent was exposed straightaway to Semi carbonization and activation temperature unlike the specific temperature progression as reported in the literature. AII experiments were conducted in a laboratory scale muffle furnace under static conditions in a self generated atmosphere covering process parameters such as impregnation ratios. We found that by using this method, the RW20% prepared with the impregnation ratio of 20% KOH had the highest Iodine Number and Methylene Blue adsorption capacity which were 72.39mg/g and 40mg/g respectively.